Guyana : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper describes economic developments in Guyana during the 1990s. Real GDP recovered with an average growth rate of 7 1\2 percent a year during 1991-94 as economic activity responded to a shift in economic policies. Renewed confidence led to increased investment-particularly increased foreign direct investment in the bauxite, gold, and forestry industries. Also, structural reforms-including the engagement of private management-led to increases in sugar and rice production, the main agricultural products. Expansion in light manufacturing, distribution, and financial services contributed importantly to the overall growth during the period.